Selection of preventive dental materials for children with special needs: Pemilihan material preventif gigi untuk anak berkebutuhan khusus - Anie Apriani; Angela Evelyna; Linda Sari Sembiring (Makassar Dental Journal, 2022)
Problems: Children with special needs often have problems in their oral health, including caries and periodontal disease. Selec-tion of good preventive dentistry materials as a whole can reduce the risk of caries and periodontal disease as well as improve the level of dental and oral health. Objectives: To describe several preventive dentistry materials that can be used in children with special needs as a protection and prevention material for their teeth and mouth. Conclusion: The selection of the right pre-ventive dentistry materials can improve the dental health status of children with special needs. These materials can be toothpaste, fluoride topical and fluoride-containing restorative materials such as glass ionomer cement.